2023
DOI: 10.1002/csc2.20989
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the generation time in winter wheat cultivars using speed breeding

Abstract: Reducing generation time is critical to achieving the goals of genetic gain in important crops like wheat (Triticum aestivum). Speed breeding (SB) has been shown to considerably reduce generation times in crop plants. Unlike spring wheat cultivars, winter wheat varieties require typically 6-9 weeks of cold treatment, called vernalization, for flowering which extends the generation time for the development of improved winter wheat cultivars. Here, we optimized the SB method using a set of 48 diverse soft red wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…1 f). Although this light intensity was lower than that of SB rooms in previous studies, which ranged from 350 to 500 µmol/m²/s [ 8 , 9 , 19 , 20 ], no significant differences in days to heading (DTH) or grain number per spike (GN) were observed between the SV + mSB and SV + SB conditions (Fig. S1 a and b).…”
Section: Resultsmentioning
confidence: 63%
“…1 f). Although this light intensity was lower than that of SB rooms in previous studies, which ranged from 350 to 500 µmol/m²/s [ 8 , 9 , 19 , 20 ], no significant differences in days to heading (DTH) or grain number per spike (GN) were observed between the SV + mSB and SV + SB conditions (Fig. S1 a and b).…”
Section: Resultsmentioning
confidence: 63%
“…So far, no research has reported the application of speed breeding against CLCuD in cotton. In addition to cotton, speed breeding has been used successfully in other cereal crops such as wheat and rice to improve disease resistance and final grain yield ( Alahmad et al, 2018 ; Chimmili et al, 2022 ; Schoen et al, 2023 ). Given the successful use of speed breeding in other crops, cotton breeders and molecular biologists are now working on its use to improve biotic and abiotic stress tolerance in cotton.…”
Section: Next-generation Sequencing Applications In Cotton Genomicsmentioning
confidence: 99%
“…Ten seeds of each genotype were sown in 4.5-inch pots with one plant per pot in a randomized complete block design. Plants were then moved into speed breeding conditions (22 hours light/2 hours dark with temperatures of 25˚C in the day and 22˚C at night) as described by Schoen et al (2023). This was done so that plants in each treatment would come to heading at the same time, reducing variables in the experiment.…”
Section: Plant Growth Conditionsmentioning
confidence: 99%